Nitric oxide and mitochondria in metabolic syndrome - Zaobornyj, Tamara (2016)
Normal cardiac function is accomplished through a continuous energy supply provided by mitochondria. Heart mitochondria are the major source of reactive oxygen and nitrogen species: superoxide anion (O2-) and nitric oxide (NO). NO production by mitochondrial NOS (mtNOS) is modified by metabolic state and shows an exponential dependence on Δψ. The interaction between mtNOS and complexes I and IV might be a mechanism involved in the regulation of mitochondrial NO production. NO exerts a high affinity, reversible and physiological inhibition of cytochrome c oxidase activity. A second effect of NO on the respiratory chain is accomplished through its interaction with ubiquinol-cytochrome c oxidoreductase. The ability of mtNOS to regulate mitochondrial O2 uptake and O2 - and H2O2 productions through the interaction of NO with the respiratory chain is named mtNOS functional activity. Together, heart mtNOS allows NO to optimize the balance between cardiac energy production and utilization, and to regulate the steady-state concentrations of other oxygen and nitrogen species.